Persuasion IQ : the 10 skills you need to get exactly what you want - Mortensen, Kurt W. (AMACOM/American Management Association, 2008)
Are you a persuasion expert? Or do you need to boost your Persuasion I.Q.? This book gives you the skills you need to become a master persuader ... and achieve anything your heart desires.